2015
DOI: 10.1007/s00464-015-4325-4
|View full text |Cite|
|
Sign up to set email alerts
|

Early laparoscopic cholecystectomy is superior to delayed acute cholecystitis: a meta-analysis of case–control studies

Abstract: Early LC is clearly superior to delayed LC in acute cholecystitis. The most recent evidence-based practice strongly suggests that early LC should be standard of care in the management of acute cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
70
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 70 publications
8
70
2
2
Order By: Relevance
“…Consequently, it does not seem to be justified to wait more than 72 h to perform LC in acute cholecystitis; it is, moreover, assertible that in agreement with the paper of Onoe et al [3], an early treatment in suitable patients leads to higher success rate, less adverse events, with shorter hospital stay, and less costs, but with technical and organization efforts. Despite the current evidences, surgical practice varies significantly worldwide, with a range of 11-89% of surgeons performing an early approach; furthermore, it is still maintained the culture that acute cholecystitis is not a surgical emergency [3].…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Consequently, it does not seem to be justified to wait more than 72 h to perform LC in acute cholecystitis; it is, moreover, assertible that in agreement with the paper of Onoe et al [3], an early treatment in suitable patients leads to higher success rate, less adverse events, with shorter hospital stay, and less costs, but with technical and organization efforts. Despite the current evidences, surgical practice varies significantly worldwide, with a range of 11-89% of surgeons performing an early approach; furthermore, it is still maintained the culture that acute cholecystitis is not a surgical emergency [3].…”
supporting
confidence: 59%
“…Similarly, also the operating time was comparable. Interestingly, Onoe et al [2] have identified at univariate analysis C-reactive protein as predictive variable for laparotomic conversion; high CRP values ([10 mg/dl) have been related to the failure to create a critical view of safety, leading to a more accurate surgical strategy choice, in relation to the individual case.Pursuing the topic, a comprehensive meta-analysis by Cao et al [3] demonstrates that these benefits will still present, although on a smaller scale, in the subgroup operated after 72 h, but within 7 days. This suggests that the ''72 h rule'' is an optimal timing; however, patients operated after this window still benefit from an early LC, rather than a non-operative management.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cao et al[43] (2015) in their meta-analyses studied if ELC is superior to DLC for ACC management. They showed that ELC group has presented reductions in mortality, bile duct complications and improvement in many other parameters analyzed.…”
Section: Timing Of Surgical Treatmentmentioning
confidence: 99%